Determination of The Most Suitable Type of Fresh Milk in Istanbul Province - Ahmet Semih Uzundumlu (Turkish Journal of Agriculture: Food Science and Technology)
The data in this study was provided from 400 households in the Kucukcekmece District of Istanbul Province in 2011. Unclustered Proportional Sampling Method was used to determine the sample size of the study. The primary objective of this study was to identify the most suitable type of milk for consumers. In determining the most appropriate type, four criteria were taken into account. These criteria are hygiene, shelf-life, nutritional content, and price. Based on the data, milk consumption was 30.2 L per annum per capita in Istanbul Province. The households consist of about 3.7 individuals, and they give importance to hygiene by 26.4 percent, shelf-life by 26.7 percent, nutritional content by 29.6 percent and price by 17.2 percent. 55.3 percent of the households prefer UHT (long of shelf-life Tetra Pac packaged milk which heat-treated range of 135-150°C in a short period of 2-4 seconds) milk, 28.5 percent prefer Pasteurized milk, and 16.2 percent prefer Raw milk. Also, while households gave more importance to price and nutrient content at the raw and pasteurized milk, shelf life and hygiene content at UHT milk. Considering these criteria, the most suitable type of milk for the consumers was UHT milk. As a result, the national companies marketing pasteurized milk in the research area need advertisement works that inform the consumers regarding pasteurized milk.